Concomitant Use of Transcranial Direct Current Stimulation and Computer-Assisted Training for the Rehabilitation of Attention in Traumatic Brain Injured Patients: Behavioral and Neuroimaging Results - Sacco, Katiuscia; Galetto, Valentina; Dimitri, Danilo; Geda, Elisabetta; Perotti, Francesca; Zettin, Marina; Geminiani, Giuliano C. (Frontiers in Behavioral Neuroscience, 2016)
Divided attention, the ability to distribute cognitive resources among two or more simultaneous tasks, may be severely compromised after traumatic brain injury (TBI), resulting in problems with numerous activities involved with daily living. So far, no research has investigated whether the use of non-invasive brain stimulation associated with neuropsychological rehabilitation might contribute to the recovery of such cognitive function. The main purpose of this study was to assess the effectiveness of 10 tDCS sessions combined with computer-assisted training; it also intended to explore the neural modifications induced by the treatment. Thirty-two patients with severe TBI participated in the study: sixteen were part of the experimental group, and sixteen part of the control group. The treatment included 20’ of tDCS, administered twice a day for 5 days. The electrodes were placed on the dorso-lateral prefrontal cortex. Their location varied across patients and it depended on each participant’s specific area of damage. The control group received sham tDCS. After each tDCS session, the patient received computer-assisted cognitive training on divided attention for 40’. The results showed that the experimental group significantly improved in divided attention performance between pre- and post-treatment, showing faster reaction times, and fewer omissions. No improvement was detected between the baseline assessment (i.e., one month before treatment) and the pre-training assessment, or within the control group. Functional magnetic resonance imaging data, obtained on the experimental group during a divided attention task, showed post-treatment lower cerebral activations in the right superior temporal gyrus (BA 42), right and left middle frontal gyrus (BA 6), right postcentral gyrus (BA 3) and left inferior frontal gyrus (BA 9). We interpreted such neural changes as normalization of previously abnormal hyperactivations.